Síndrome de burnout y resiliencia por covid-19 en enfermeras, Hospital General José María Velasco Ibarra. Tena, 2021 - Jemima Abigail, Chiluiza Becerra (2021)
ABSTRACT The current research aimed to analyze the burnout and resilience syndrome due to covid-19 in nurses at Hospital General José María Velasco Ibarra in Tena. The project corresponds to a non-experimental cross-sectional design, field, and descriptive level, with 170 female nurses from the hospital. The psychological instruments used were: Maslach Burnout Inventory (MBI) to determine the subscales in emotional exhaustion, depersonalization, and personal fulfillment, as well as the presence or absence of the syndrome and the Wagnild and Young Resilience Scale, to know the levels of resilience to the burnout in every nurse. Among the most relevant results, it was obtained that 17.6% presents burnout syndrome and 82.4% does not present the syndrome, within the dimensions, 54.1% has low emotional exhaustion, 41.2% present moderate levels of depersonalization, and 47.1% has low levels of personal fulfillment. However, 98.2% of the sample indicates having high levels of resilience, while 1.8% has low levels of resilience. These results confirmed that high levels of resilience act as a protective factor in the burnout syndrome present in nurses during covid-19. Keywords: burnout syndrome, resilience, covid-19, psychological instruments. Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258